2023
DOI: 10.1101/2023.04.11.536377
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The RNA binding proteins LARP4A and LARP4B promote sarcoma and carcinoma growth and metastasis

Abstract: RNA-binding proteins (RBPs) are emerging as important regulators of pathogenesis, including cancer. Here we reveal that the recently characterised RBPs LARP4A and LARP4B are differentially overexpressed in primary osteosarcoma and osteosarcoma lung metastases, as well as in prostate cancer. Depletion of LARP4A and LARP4B inhibited primary tumour growth and metastatic spread in xenograft studies, as well as inhibiting cell proliferation, motility and migration. Transcriptomic profiling combined with high conten… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 92 publications
2
2
0
Order By: Relevance
“…4 B). This is consistent with a recent study which showed that depletion of LARP4 in osteosarcoma cancer lines (MNNG/HOS; MG63) also reduced cell proliferation ( Coleman et al 2023b ). These data indicate that LARP4 is required for normal rates of proliferation in HEK293 cells and that LARP4 depletion is also associated with reduced proliferation rates in the osteosarcoma cancer cell line U2OS.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…4 B). This is consistent with a recent study which showed that depletion of LARP4 in osteosarcoma cancer lines (MNNG/HOS; MG63) also reduced cell proliferation ( Coleman et al 2023b ). These data indicate that LARP4 is required for normal rates of proliferation in HEK293 cells and that LARP4 depletion is also associated with reduced proliferation rates in the osteosarcoma cancer cell line U2OS.…”
Section: Resultssupporting
confidence: 93%
“…However, because mRNA abundance is a product of both stability and transcription rate, it remains a possibility that changes in the transcriptional rate of LARP4 target mRNAs could be masking the role of LARP4 in regulating target mRNA stability. Given that recruitment of LARP4 to the cytoplasmic surface of the mitochondria has been previously demonstrated ( Gabrovsek et al 2020 ; Coleman et al 2023b ) and we demonstrated that mitochondria-associated translation was reduced upon LARP4 depletion, LARP4 may play a direct role in the recruitment of a subset of its target mRNAs to the vicinity of the mitochondria to enhance their local translation and mitochondrial protein targeting. Additionally, both our proteomic analysis and immunofluorescence staining analysis of LARP4-depleted cells demonstrated nonmitochondrial accumulation of protein products encoded by mitochondrial RNA targets of LARP4, implicating LARP4 in the process of mitochondrial protein targeting.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations